Hemoglobin Status of the Hospital Admitted Patients: A Cross-Sectional Study in A District Hospital of Bangladesh - Debnath, Asish Kumar; Rahman, Md Khalilur; Haque, Md Azizul; Islam, Md Nurul (TAJ: Journal of Teachers Association, 2022)
Introduction: Anemia is a global public health concern, especially in lower and middle income countries like Bangladesh. The present study aimed to find out the hemoglobin level and prevalence of anemia among the patients admitted in a district hospital of Meherpur, Bangladesh. Methods: This cross sectional study was conducted among 500 patients admitted to Medicine and Gynecology department of Meherpur General Hospital. After enrollment, 2-3 ml of blood sample was collected in EDTA tubes from each patients and hemoglobin level was determined using an automated hematology analyzer for determination of anemia as defined by the WHO. All statistical analyses were carried out using SPSS version 24.0 for a significant p-value <0.05. Results: The mean (SD) age of the participants was 48.6 (18.9) years and almost 57% of them were female. Mean (SD) of the Hb level among the participants was 9.8 (1.7) g/dL which was significantly higher among men compared to women (10.1 mg/dL vs 9.5mg/dL). Overall prevalence of anemia was 93.8% (mild 25%, moderate 54% and severe 15%) and the prevalence was comparatively higher among women (96% vs 91%). Female sex and older age were significant risk factors of moderate to severe anemia among the participants though other variables like comorbidities and chronic NSAID use were not revealed as significant. Conclusion: Anemia prevalence was very high among the patients admitted in Meherpur district hospital, especially among female and elderly patients. So, routine assessment and proper management of anemia of the hospital admitted patients is crucial for better treatment outcome. TAJ 2021; 34: No-2: 114-121